2002
DOI: 10.1086/344462
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors ofToxoplasmaSeropositivity in Women with and at Risk for Human Immunodeficiency Virus Infection

Abstract: We assessed the prevalence and predictors of latent Toxoplasma infection in a large group of human immunodeficiency virus (HIV)-infected and HIV-uninfected at-risk US women. The prevalence of latent Toxoplasma infection was 15% (380 of 2525 persons) and did not differ by HIV infection status. HIV-infected women aged > or =50 years and those born outside of the United States were more likely to have latent Toxoplasma infection, with prevalences of 32% and 41%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 11 publications
5
30
0
3
Order By: Relevance
“…6,12,16 This extends the vulnerability in this population, including the increased risk of vertical transmission not only of HIV, but also of T. gondii. 4,15 Risk factors in this population reflect the data in the literature and the social, economic and cultural context of Mozambique. 19 Prevalence estimates of latent infections by T. gondii in HIV-infected patients showed a wide variation in the risk factors and ethnicity factors including classic factors such as those evaluated in this study, in terms of exposure to soil, animals and meat intake.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…6,12,16 This extends the vulnerability in this population, including the increased risk of vertical transmission not only of HIV, but also of T. gondii. 4,15 Risk factors in this population reflect the data in the literature and the social, economic and cultural context of Mozambique. 19 Prevalence estimates of latent infections by T. gondii in HIV-infected patients showed a wide variation in the risk factors and ethnicity factors including classic factors such as those evaluated in this study, in terms of exposure to soil, animals and meat intake.…”
Section: Discussionmentioning
confidence: 53%
“…4 Even in the era after the introduction of HAART, it still represents important public health problem, especially to vulnerable populations in developing and developed countries. 2 This study has important implications, considering the possibility of reducing morbidity and mortality and increased survival in patients infected with HIV/AIDS with the adoption and development of HAART, both in adults and in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age and race/ethnicity, among other demographic characteristics, were shown to have a positive interaction with this parasite. A study from the United States demonstrated that Toxoplasma prevalence rates reported in HIV-infected women aged  50 years were significantly higher compared to those who were younger (Falusi et al, 2002). This was dissimilar to a study from Malaysia which reported that HIV-infected patients in the younger age group had higher Toxoplasma seroprevalence rates than the older age group although it was not statistically significant .…”
Section: Epidemiology -From Source To Genementioning
confidence: 73%
“…7,8 For example, nearly one-third (30%) of all AIDS patients with seropositivity to this organism who experienced CD4 counts below 100 cells/mm 3 have developed reactivated toxoplasmosis, especially in the absence of effective prophylaxis. 9 In non-HIV immune suppression (e.g., from cancer chemotherapy, prolonged steroid treatment of connective tissue disorders, post-transplantation therapy, or poorly controlled diabetes), this disease risk is still substantial but generally not as wellcharacterized in the literature. [10][11][12] To contribute to this latter gap in the literature, we conducted a multipart study using the national multiple cause of death (MCD) dataset from 2000 to 2010: (part 1) quantification and trend analysis of toxoplasmosis mortality in the United States, (part 2) a matched case-control analysis matching associated medical conditions to disease cases and (part 3) a cost analysis to enumerate the cumulative productivity losses attributed to pre-mature death from this zoonosis during the 11-year study period.…”
Section: Introductionmentioning
confidence: 99%